ANALYSIS OF CAUSES OF SUBSIDENCE IN THE AREA NEAR UJUNGNEGORO STATION, BATANG REGENCY - Wisyanto Wisyanto (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2021)
Changes in human activities from time to time increase rapidly. This activity requires the support of a reliable transportation network. Railroad land transportation is the main choice to overcome the impasse of human mobility and distribution of goods. It is known that this type of transportation does not intersect with other means of transportation so that it is free from congestion. For the sake of smoothness and safety in the use of trains, proper maintenance of the rail network is needed. Land subsidence supporting the railroad tracks is a common event that disrupts the functioning of the railroad and is part of maintenance. One of the subsidence that often occurs on the railroad tracks is a subsidence on the railroad tracks around Ujungnegoro Station. To find out the cause, an analysis of geoelectric data, groundwater basin conditions and local topography has been carried out on it. The results of the analysis that have been carried out conclude that the clay content factor and the concentration of water flow are the main factors causing subsidence.